2022
DOI: 10.1093/bjd/ljac010
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease: assessing quality-of-life impacts in hyperhidrosis

Abstract: With this study it can be concluded that a substantial number of severe axillary HH patients suffers from a tremendous impairment in their QoL. In comparison to other dermatological conditions, the burden of disease in hyperhidrosis is quite high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Since the impact of HH on quality of life is comparable or even worse than in other major skin diseases, 7,24,25 we chose to assess quality of life as an important patient-reported outcome measure to assess the therapeutic effect of 1% GPB cream. HDSS, HidroQoL© and DLQI demonstrated a significant improvement in the quality of life over the entire study period of 72 weeks compared to baseline assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the impact of HH on quality of life is comparable or even worse than in other major skin diseases, 7,24,25 we chose to assess quality of life as an important patient-reported outcome measure to assess the therapeutic effect of 1% GPB cream. HDSS, HidroQoL© and DLQI demonstrated a significant improvement in the quality of life over the entire study period of 72 weeks compared to baseline assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the quality of life in patients with and without HH showed that the prevalence of depression and anxiety was significantly higher in patients suffering from HH 6,7 . These findings prove that HH, especially primary axillary HH (PAHH), is not only bothersome but also a serious medical issue for the affected patients and requires appropriate treatment.…”
Section: Introductionmentioning
confidence: 88%